A DILEMMA‐FOCUSED INTERVENTION FOR DEPRESSION: A MULTICENTER, RANDOMIZED CONTROLLED TRIAL WITH A 3‐MONTH FOLLOW‐UP. Issue 9 (22nd April 2016) - Feixas, Guillem; Bados, Arturo; García‐Grau, Eugeni; Paz, Clara; Montesano, Adrián; Compañ, Victoria; Salla, Marta; Aguilera, Mari; Trujillo, Adriana; Cañete, José; Medeiros‐Ferreira, Leticia; Soriano, José; et al.
Abstract : Background: Since long ago it has been asserted that internal conflicts are relevant to the understanding and treatment of mental disorders, but little research has been conducted to support the claim. The aim of this study was to test the differential efficacy of group cognitive behavioral therapy (CBT) plus an intervention focused on the dilemma(s) detected for each patient versus group individual CBT plus individual CBT for treating depression. A comparative controlled trial with a 3‐month follow‐up was conducted. Methods: One hundred twenty‐eight adults meeting criteria for MDD and/or dysthymia, presenting at least one cognitive conflict (implicative dilemma or dilemmatic construct, assessed by the repertory grid technique) and who had completed seven sessions of group CBT were randomly assigned to eight sessions of individual manualized CBT or dilemma‐focused therapy (DFT). The Beck Depression Inventory‐II was administered at baseline, at the end of therapy and after 3 months' follow‐up. Results: Multilevel mixed effects modeling yielded no significant differences between CBT and DFT with the intention‐to‐treat sample. Equivalent effect sizes, remission, and response rates were found with completers as well. In combination with group CBT, both individual CBT and DFT significantly reduced depressive symptoms. Conclusions: Both conditions obtained comparable results to those in the literature. Thus, the superiority of the adjunctive DFT was not demonstrated. Working with dilemmas can be seen as a promising additional target in the psychotherapy of depression, but further research is still required.